SOCIAL REHABILITATION OF PEOPLE WITH INTELLECTUAL DISABILITIES USING ART THERAPY METHODS - Shlat, Natalia; Borisov, Boris; Shakirova, Nadezhda; Shpak, Aleksej (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article considers the problem of social rehabilitation of people with intellectual disabilities: analyzes the category of «disability» as a social phenomenon, summarizes the current approaches and social practices of foreign and Russian scientific schools in the context of the problem being studied, theoretically reveals the potential of art–therapeutic methods in organizing social rehabilitation of people with disabilities in accordance with the specifics of disabilities.The article describes an empirical study, in the course of which the features of social orientation of people with intellectual disabilities, their adaptive mechanisms and creative potential are revealed. The material of the article includes a description of the author's project “Art without Borders”, aimed at the socio–cultural rehabilitation of people with intellectual disabilities and the development of their creative potential using art therapy methods. The results of the study can be the basis for designing a system of social rehabilitation of people with intellectual disabilities.